Pneumococcal conjugate 7-valent vacciPNEUMOCOCCAL CONJUGATE 7-VALENT VACCINE IN CHILDREN. REGIONAL EXPERIENCEne in children. Regional experience - N. L. Chernaya; O. B. Dadayeva; V. M. Ganuzin; G. S. Ganuzina; S. E. Batorshina; I. V. Ivanova (Union of pediatricians of Russia, 2012)
Paper is devoted to one of the most actual problems of early childhood - a pneumococcal infection. The unique preventive way is vaccination. The authors have demonstrated their own experience with pneumococcal conjugate 7-valent vaccine in 196 children 1-5 years old. A comparative analysis of children's reactions to the vaccine, depending on their age and health status was done. The results showed the low vaccine reactogenicity, its safety in children with various disorders. Severe vaccine-related vaccination reactions and complications were not documented.